You can't put a value on that… Or can you? Economic evaluation in simulation‐based medical education. Issue 2 (22nd January 2018) - Nestel, Debra; Brazil, Victoria; Hay, Margaret
Abstract : Nestel and colleagues use Lin et al.'s analysis of economic evaluation in simulation‐based medical education to question the heterogeneity of ways in which "value" can be defined